Triplet sensitization via charge recombination at organic heterojunction for efficient near-infrared to visible solid-state photon upconversion - Yuji Sakamoto; Seiichiro Izawa; Hideo Ohkita; Masahiro Hiramoto; Yasunari Tamai (Communications Materials, 2022)
A near-infrared to visible photon upconversion device was previously shown to increase external quantum efficiency by up to 2.3%. Here, the upconversion mechanism is studied by time-resolved spectroscopy, revealing that 67% of incident photons are utilized.